Spatiotemporal Assessment of LULC Changes Using Remote Sensing Approaches - Kalaycı Kadak, Merve (Journal of Agricultural Production, 2025)
The study examines changes in Land-Use/Land-Cover (LULC) in the Yenişehir district of Bursa province (Türkiye) between 2020 and 2024. Focusing specifically on the loss of agricultural land due to anthropogenic pressure, the study aims to identify changes in the LULC using remote sensing tools and techniques. In this regard, it aims to contribute to the development of sustainable land use policies. High-resolution Dynamic World dataset generated from Sentinel-2 satellite imagery was employed. The study, which was conducted by using Google Earth Engine (GEE) and ArcGIS Pro, generated annual LULC maps, inter-class transition maps that focus on agricultural land for consecutive years, and annual NDVI maps. As a result, a total of 2% decrease was detected in the crops class, accelerating particularly after 2022. NDVI values also decreased in the same areas, displaying similarity to this result. The findings are generally observed in agricultural land in peri-urban areas and are associated with both anthropogenic pressure and climate change impacts on the agricultural landscape. The study, based on data analyses, emphasizes the importance of ecology-based strategic approaches and demonstrates the need to integrate these approaches into spatial planning. Moreover, it shows the applicability of Dynamic World dataset in short-term monitoring of surface area losses in agricultural areas.